PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK - Lhony Laisnima; Krisna Isya Mandosir (Arfak Chem: Chemistry Education Journal, 2020)
The education system is having problems, especially the low quality of education. This matter  could be caused by the ineffective learning process, so we need an  steps that can improve students' understanding of the subject matter. Process changed to use the learning model with Discovery Learning. This study aims used  determine the effect of using the model  Learning Discovery Learning about cognitive learning outcomes of students in the subject matter  chemistry class X IPA SMA Kristen YABT Manokwari. The research method used  is a Quasi Experimental with the form of Time Series Design. Sampling technique  using saturated sampling with a sample size of fifteen people. Data collection tools  is a test of cognitive learning outcomes. Based on the results of data processing obtained, the average score  The pre-test is 53.78 and the average score post-test is 68, and the N-Gain result is obtained  shows an increase in the learning ability of students between before being treated and  after being given treatment that is 0.73. Based on the Paired Sample T-test, it was found that  there is an effect of using the learning model Discovery Learning on the results  cognitive learning of students on the subject matter of chemical bonding class X IPA SMA Kristen YABT  Manokwari with a large influence of 30%. Keywords: Learning model, discovery learning, outcomes learning, cognitive, Quasi Experimental